2012
DOI: 10.1152/ajpgi.00024.2012
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG culture supernatant ameliorates acute alcohol-induced intestinal permeability and liver injury

Abstract: Endotoxemia is a contributing cofactor to alcoholic liver disease (ALD), and alcohol-induced increased intestinal permeability is one of the mechanisms of endotoxin absorption. Probiotic bacteria have been shown to promote intestinal epithelial integrity and protect barrier function in inflammatory bowel disease (IBD) and in ALD. Although it is highly possible that some common molecules secreted by probiotics contribute to this action in IBD, the effect of probiotic culture supernatant has not yet been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
190
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(205 citation statements)
references
References 65 publications
14
190
0
1
Order By: Relevance
“…Notably, LGG has been shown to improve gut permeability (Wang et al, 2012;Sindhu et al, 2014). In this study, modulation of gut microbiota and permeability by LGG (with an associated reduction in endotoxemia and TLR-4 activation) may have lowered FOXO1 skin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, LGG has been shown to improve gut permeability (Wang et al, 2012;Sindhu et al, 2014). In this study, modulation of gut microbiota and permeability by LGG (with an associated reduction in endotoxemia and TLR-4 activation) may have lowered FOXO1 skin expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, L. rhamnosus treatment modulates the immune system (Forsythe et al, 2012;Karimi et al, 2009;Kozakova et al, 2016;Ma et al, 2004), intestinal motility , gut barrier function (Patel et al, 2012;Wang et al, 2012) and enteric nervous system (Kamiya et al, 2006;Ma et al, 2009). Taken together, these preclinical studies identify L. rhamnosus as a candidate psychobiotic with the one of the most comprehensive behavioural, physiological and neurobiological profiles.…”
Section: Introductionmentioning
confidence: 93%
“…It also has been observed the alcoholic liver injury in rats is associated with increased levels of plasma endotoxin (Mathurin et al, 2000;Tsukamoto et al, 2008). Furthermore, administration of antibiotics (Adachi et al, 1995) and probiotic bacteria (Wang et al, 2012) to rodents reduces the growth of Gram-negative bacteria in the intestinal lumen and prevents EtOH-induced endotoxemia and liver injury. It has been suggested that in ALD the endotoxin levels at specific locations such as in portal blood might be more important than the levels in systemic plasma (Lambert et al, 2003).…”
Section: Inhibition Of Endotoxin Signaling Pathway By Puerarin In Aldmentioning
confidence: 98%